Cloud Computing Technology in Development E-Business (Literature Review) - Fitri, Liana Syah; Elinca; Larisma, Ena; Natalia; Levina , Britney (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
Good use of technology will be able to help various kinds of work activities including in the business world. High mobility requires a person or group to use information technology. One of the topics of technological development today is cloud computing. Cloud computing is a technology that uses the internet network to access resources in the process of managing data, processing data to its application. Cloud computing is widely used by people to start a business because it has many advantages in starting a business. One of the new concepts offered is e-business or electronic business. E-business is an expanded form of e-Commerce, where e-business is accompanied by customer service, collaboration with business partners with electronic support as a means of transaction or organization, but not only purchases, payments for goods, and services, but also Cloud computing services allow companies to determine the capacity to meet demand and move according to the speed of business growth of the company but not at a speed determined by enterprise infrastructure. This allows companies to generate better time to market, speed up application delivery and ensure management of capital or operational costs. Cloud computing implementation in business requires consideration of business and IT requirements as well as selecting available cloud computing to formulate the right cloud strategy. The goal after the implementation of cloud computing is that users can expand cloud computing capabilities more efficiently. In addition to having the advantages of cloud computing, it also has risks, namely only providers who know physically what is happening with user data, when disasters occur sometimes the ability of providers to recover data is still a concern for users, and provider compliance with regulations and when experiencing bankruptcy is still uncertain.